A Prism-Mask System for Multispectral Video Acquisition - Cao, Xun; Du, Hao; Tong, Xin; Dai, Qionghai; Lin, Steve (IEEE Transactions on Pattern Analysis and Machine Intelligence, 2011)
This paper presents a prism-mask system for capturing multispectral videos. The system is composed of a triangular prism, a monochrome camera, and an occlusion mask. Incoming light beams from the scene are sampled by the occlusion mask, dispersed into their constituent spectra by the triangular prism, and then captured by the monochrome camera. Our system is capable of capturing frames with high spectral resolution at video rates. It also allows for different trade-offs between spectral and spatial resolution by adjusting the focal length of the camera. We demonstrate multispectral video acquisition with various spectral resolutions and spatial resolutions, as well as different frame rates. The effectiveness of our system is further evaluated with several applications, including human skin detection, physical material recognition, video segmentation, RGB video generation, and illumination identification.